2021
DOI: 10.1155/2021/6691958
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Molecular Subtypes of Breast Cancer with Mammography and Ultrasound Findings: Introduction of Sono-Mammometry Score

Abstract: We studied the correlation of sonographic and digital mammographic features with molecular classification of breast cancer. Imaging features from 313 patients with preliminary ultrasound and digital mammogram between November 2017 and May 2020 were compared with histopathology and immunohistochemical analysis for the prediction of molecular classification of breast cancer. We also devised a score called “sono-mammometry” score consisting of few simple imaging features which can easily be performed in outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…Logistic regression analysis showed that Basal-like breast cancer was mostly characterized by regular shape, circumscribed margins and abnormal lymph nodes ( P <0.05). This is supported by previous studies ( 32 – 34 ). This may be due to the high degree of malignancy of Basal-like breast cancer, relatively fast growth, tumor cell growth in the marginal zone, and less connective tissue response ( 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…Logistic regression analysis showed that Basal-like breast cancer was mostly characterized by regular shape, circumscribed margins and abnormal lymph nodes ( P <0.05). This is supported by previous studies ( 32 – 34 ). This may be due to the high degree of malignancy of Basal-like breast cancer, relatively fast growth, tumor cell growth in the marginal zone, and less connective tissue response ( 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…The angular/spiculated margin and posterior acoustic attenuation are well-known typical sonographic features of malignant breast tumors. The angular/spiculated margin is believed to be associated with the low proliferation rates of malignant cells, which allow enough time to have stromal interactions and induce fibrosis surrounding the invasive edge [ 44 ]. The fibrosis as well as the disorganized growth of malignant cells lead to an increase in acoustic impedance that causes posterior acoustic attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…It forms a blurred mixed zone between the tumor and the tissues and complex edge. Besides, the complex interstitial components and hyaline transformation of malignant lesions often lead to scattering of acoustic signals [ 10 , 11 ]. During the decision process, the specialists often consider the orientation, posterior shadowing (PS), edge indistinctness (EI), and shape complexity (SC) of the tumors as essential features to identify them as benign or malignant.…”
Section: Methodsmentioning
confidence: 99%
“…But here we only use the first moment as it is sufficient to provide a score that could differentiate PS regions of different BUS images effectively. Accordingly, we substituted p � 0 and q � 2 in equation (11) and defined the PS score as…”
Section: Computation Of the Ps Score Of Posterior Shadowingmentioning
confidence: 99%